2006
DOI: 10.3989/scimar.2006.70s1183
|View full text |Cite
|
Sign up to set email alerts
|

Growth and condition of juvenile sole (<em>Solea solea</em> L.) as indicators of habitat quality in coastal and estuarine nurseries in the Bay of Biscay with a focus on sites exposed to Erika oil spill

Abstract: SUMMARY: Indicators of growth and condition were used to compare the habitat quality of nurseries of juvenile sole (Solea solea L.) in the Bay of Biscay, based on one survey in 2000. The four biological indicators are poorly correlated with each other, suggesting that no single measure may give an adequate description of fish health and of its habitat's quality. Growth indicators showed significant differences between northern and southern areas. Juveniles from the two southernmost nurseries, the Gironde estua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
1
20
0
4
Order By: Relevance
“…However, according to GLMs, density of juvenile plaice in the area showed no significant effect on RNA/DNA values. This agrees withGilliers et al (2006) who found no evidence for density-dependent effects on juvenile sole S. solea condition in the Bay of Biscay. Thus, other factors, which were not considered in the present study, are probably the cause of variability.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…However, according to GLMs, density of juvenile plaice in the area showed no significant effect on RNA/DNA values. This agrees withGilliers et al (2006) who found no evidence for density-dependent effects on juvenile sole S. solea condition in the Bay of Biscay. Thus, other factors, which were not considered in the present study, are probably the cause of variability.…”
supporting
confidence: 93%
“…Mehner & Wieser (1994) reported that in response to the stress of starvation, animals may reduce their resting metabolic rate and direct energy reserves away from growth into the support of vital processes. As reported by Gilliers et al (2006), the different time of response of biological indices suggests that no single measure may give an adequate description of fish habitat's quality. Compared with results reported by other authors, the sensitivity of the biological indices measured on juvenile plaice is in accordance with the literature.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, after being released into the pond, the sole recovered a better condition and growth. Within 160 days, they reached the maximum K observed in the Bay of Biscay in late summer (∼1.3 g cm −3 in Gilliers et al 2006). Those high growth performances and condition level were achieved at high fish densities (300 sole 1000 m −2 ) as compared with commonly estimated densities on main nursery grounds (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…In the Bay of Biscay, the main nursery grounds have been localised in estuaries and bays from yearly autumn surveys (Le Pape et al 2003a). Comparison of various biological indicators indicated quality differences between nurseries, depending on the particular estuary or bay location (Le Pape et al 2003b;Gilliers et al 2006). In embayed nursery areas, and especially in the Pertuis Breton (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, density is less variable, food limitation is more obvious (Duncan and Holland 2006), and growth is less biased due to size-dependent selection (Meng et al 2000;Le Pape et al 2003a;Gilliers et al 2006;Amara et al 2007Amara et al , 2009Selleslagh and Amara 2013). Indeed, density is less variable, food limitation is more obvious (Duncan and Holland 2006), and growth is less biased due to size-dependent selection (Meng et al 2000;Le Pape et al 2003a;Gilliers et al 2006;Amara et al 2007Amara et al , 2009Selleslagh and Amara 2013).…”
Section: Implication Of Food Limitation For Management Of Essential Nmentioning
confidence: 99%